Arthroscopic Posterior Glenoid Fracture Fixation Using Knotless Suture Anchors - Baxter, Jonathan A.; Tyler, James; Bhamber, Nivander; Arnander, Magnus; Pearse, Eyiyemi; Tennent, Duncan (Arthroscopy techniques (Amsterdam), 2017)
Shoulder instability after a posterior glenoid rim fracture is rare and potentially difficult pathology to treat. Operative techniques often involve a large dissection to view the fragments resulting in local soft tissue injury. Internal fixation is often achieved with interfragmentary screws; however, this may not be possible with small or multifragmentary fracture patterns. We describe an arthroscopic technique for posterior glenoid rim fracture fixation using knotless suture anchors. These anchors can be inserted without cannulas allowing easier access to the posterior glenoid. This procedure is simple, safe, and offers good visualization of the glenohumeral joint whilst avoiding the detrimental effects of larger surgical dissection.